Moving forward with innovation: taking dentistry to new frontiers / Nik Mohd Mazuan Nik Mohd Rosdy ... [et al.] - Nik Mohd Rosdy, Nik Mohd Mazuan; Md Sabri, Budi Aslinie; Yusof, Norashikin; Md Bohari, Nor Faezah; Mohd Radzi, Nawwal Alwani; Md Yani, Azri Aliah; Hassan, Eddy Hasrul; Harun, Nurharnani; Shoji, Yoshinobu; Mohd Yusof, Mohd Yusmiaidil Putera (2023)
Background: The oral healthcare landscape is ever changing, and it needs new and innovative solutions more than ever. The continuous demand for improved quality treatment and prevention, efficient service and improved prognosis and outcomes requires the dental industry to be proactive in accelerating inventions and innovations for the betterment of oral health care.